2001
DOI: 10.1016/s0301-0546(01)79043-x
|View full text |Cite
|
Sign up to set email alerts
|

NSAID intolerance in chronic idiopathic urticaria: A study of its relationship with histamine-releasing activity of patients’ sera

Abstract: in patients with CIU intolerance to NSAID does not depend on the mechanism of histamine release.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 18 publications
0
7
1
Order By: Relevance
“…Our results in a case population from Turkey revealed a lower incidence (38.2%) of autoreactivity in CIU when compared to those of the previous studies from other countries (2, 810, 13, 14, 16). However, the positivity of ASST in NSAID intolerant CIU patients ( i.e.…”
Section: Discussioncontrasting
confidence: 60%
See 3 more Smart Citations
“…Our results in a case population from Turkey revealed a lower incidence (38.2%) of autoreactivity in CIU when compared to those of the previous studies from other countries (2, 810, 13, 14, 16). However, the positivity of ASST in NSAID intolerant CIU patients ( i.e.…”
Section: Discussioncontrasting
confidence: 60%
“…It also remains to be explained which mechanisms underlie the increased LT 4 de novo production after ASST in patients with severe CIU (14). A putative mechanism for NSAID‐induced exacerbation in CIU has been proposed to be an increased activity of LTC 4 synthase (2), which is a key enzyme for the production of cysteinyl leukotrienes, because a fivefold increase in LTC 4 synthase positive cells has been shown in the majority of the patients with aspirin‐induced asthma (18). On the other hand, some anecdotal case reports (1923) and study results (24, 25) have shown that LT receptor antagonists montelukast and zafirlukast were effective in the treatment of CIU, particularly in the control of severe urticaria/angioedema exacerbations related to cold, pressure, food additives, and NSAIDs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The prevalence of NSAIDs intolerance seems to be similar in ASST + and ASST − patients with CU (65). However, a high proportion (91–93%) of patients presenting with new onset urticaria after the ingestion of several chemically unrelated drugs have a positive ASST (16, 17).…”
Section: Nsaids Intolerance Multiple Drug Allergy Syndrome and Asstmentioning
confidence: 99%